Analisis Potensi Pengembangan Wisata Halal: Studi Kasus pada Wisata Alam Sumbermaron - Rozi, A. Fahrur; Anam, Ahmad Khoirul (Jihbiz : Jurnal Ekonomi, Keuangan dan Perbankan Syariah, 2024)
This study aims to determine and analysis the potential for halal tourism development at the Sumbermaron Nature Tourism Destination, Karangsuko Village, Pagelaran District, Malang Regency. This study used the descriptive-qualitative method. The results of the study show that aspects of tourism development are progressing quite well, as evidenced by the increase in the number of tourists visits each year. The potential for the development of halal tourism is analyses based on indicators from the Global Muslim Travel Index (GMTI). There are several indicators that have quite potential, such as the service aspect, where the existing services at tourist destinations are in accordance with the concept of service in Islam. As for the aspects of opportunities and challenges in the development of halal tourism, namely geographically located in the area of Islamic boarding schools, which can be used as opportunities in developing halal tourism, as for the challenges, namely the absence of halal labelling on food and drinks sold, related to worship facilities that are not yet in accordance with development standards for halal tourism, this is due to a lack of public knowledge about the concept of halal tourism.